Addressing the burden of dialysis around the world: A summary of the roundtable discussion on dialysis economics at the First International Congress of Chinese Nephrologists 2015. (20th November 2017) - Li, Philip Kam‐Tao; Lui, Sing Leung; Ng, Jack Kit‐Chung; Cai, Guan Yan; Chan, Christopher T; Chen, Hung Chun; Cheung, Alfred K; Choi, Koon Shing; Choong, Hui Lin; Fan, Stanley L; Ong, Loke Meng; Yu, Linda Wai Ling; et al.
Summary at a Glance: The First International Congress of Chinese Nephrologists was held in Hong Kong in 2015. This review summarizes the results of a roundtable discussion among international experts in order to cope with the ever‐increasing prevalence of end stage renal disease and the resulting heavy dialysis burden. ABSTRACT: To address the issue of heavy dialysis burden due to the rising prevalence of end‐stage renal disease around the world, a roundtable discussion on the sustainability of managing dialysis burden around the world was held in Hong Kong during the First International Congress of Chinese Nephrologists in December 2015. The roundtable discussion was attended by experts from Hong Kong, China, Canada, England, Malaysia, Singapore, Taiwan and United States. Potential solutions to cope with the heavy burden on dialysis include the prevention and retardation of the progression of CKD; wider use of home‐based dialysis therapy, particularly PD; promotion of kidney transplantation; and the use of renal palliative care service.